Anabolic Androgenic Steroids and Hepatocellular Adenoma and Carcinoma: Molecular Mechanisms and Clinical Implications - Luca Ielasi; Enrico Fulco; Nicola Reggidori; Marco Domenicali; Francesco Giuseppe Foschi (Gastroenterology Insights, 2024)
Anabolic androgenic steroids (AAS) are a class of hormones that are used for hormonal replacement therapy in cases of male hypogonadism and for a few other medical conditions, mainly anemias, as well as for the female-to-male transition process. At the same time, AAS are widely abused for their muscle-building and strength-increasing properties. Among their side effects, androgens can exert a toxic effect on the liver, causing hepatotoxicity, but they can also induce hepatocyte proliferation and malignant transformation. Hepatocellular adenoma (HCA) and hepatocellular carcinoma (HCC) are two primary liver lesions that have been described as potentially related to AAS. This review provides an up-to-date analysis of how androgens can induce liver carcinogenesis and a comprehensive overview on the available data in the literature about AAS and primary liver tumors.